2005
DOI: 10.1017/s0265021503000073
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal intubation without muscle relaxants: remifentanil or alfentanil in combination with propofol

Abstract: Remifentanil 4 microg kg(-1) and propofol 2 mg kg(-1) administered in sequence intravenously provided good or excellent conditions for tracheal intubation in all patients without the use of muscle relaxants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 271 publications
0
35
2
Order By: Relevance
“…[7][8][9] Moreover, high rates of good to excellent intubating conditions have been reported without the use of NMBDs, provided that the anesthetic induction protocol is optimized with an adequate dose of an opioid analgesic co-administered with either propofol or thiopental. [10][11][12][13][14][15][16] Due to its rapid onset, remifentanil 2 µg·kg -1 , combined with propofol 2 mg·kg -1 , provides acceptable intubating conditions in 75 to 85% of patients. 11,12 However, no previous study has evaluated potential laryngeal morbidity associated with an optimized relaxant-free anesthetic induction protocol.…”
Section: Conclusion : à La Suite D'une Induction De L'anesthésie à L'mentioning
confidence: 99%
“…[7][8][9] Moreover, high rates of good to excellent intubating conditions have been reported without the use of NMBDs, provided that the anesthetic induction protocol is optimized with an adequate dose of an opioid analgesic co-administered with either propofol or thiopental. [10][11][12][13][14][15][16] Due to its rapid onset, remifentanil 2 µg·kg -1 , combined with propofol 2 mg·kg -1 , provides acceptable intubating conditions in 75 to 85% of patients. 11,12 However, no previous study has evaluated potential laryngeal morbidity associated with an optimized relaxant-free anesthetic induction protocol.…”
Section: Conclusion : à La Suite D'une Induction De L'anesthésie à L'mentioning
confidence: 99%
“…The chosen anesthetic regimen, sevoflurane and remifentanil, might have been a reason for the ease of positive pressure ventilation despite the absence of neuromuscular blockade in the NOBLOCK group. Remifentanil is known to facilitate even endotracheal intubation without the aid of neuromuscular blocking agents 7,8 and its ability to profoundly block the nociceptive reaction could have helped to easily tolerate positive pressure ventilation. The chosen induction regimen of propofol 2.5 mg·kg -1 two minutes after remifentanil infusion possibly created a sufficient depth of anesthesia for successful LMA insertion.…”
Section: Me Et Th Ho Od Ds Smentioning
confidence: 99%
“…Several previous studies reported a similar acceptable decrease in the MAP and HR when using varying amounts of remifentanil (from 0.5 to 5 lgÁkg -1 ) combined with propofol 2.0 or 2.5 mgÁkg -1 . 23,26 In fact, in ASA I and II patients, it has been reported that co-administration of fentanyl (2 or 4 lgÁkg -1 ) with increased doses of propofol (from 2 to 3.5 lgÁkg -1 ) did not exacerbate a decrease of either blood pressure or HR while it attenuated the cardiovascular response to laryngoscopy in comparison with placebo. 19 In the same way, the addition of remifentanil 0.25 or 0.5 lgÁkg -1 to propofol 2.5 mgÁkg -1 was well tolerated and moderated cardiovascular responsiveness to LMA insertion that were present when no opioid was co-administered with propofol.…”
Section: Discussionmentioning
confidence: 99%